Relationship of Neutrophil to Lymphocytis Ratio with Success of Thrombolysis in Patients of STEMI - Asma Kamal, Shazia Siddique, Khadija Muneer, Asifa Kamal, Mahrukh Mansoor Khosa, Aneeqa Ilyas, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the frequency of success of thrombolysis using SK in patients of STEMI, To investigate the association of success of thrombolysis with NLR in patients of STEMI. Methodology: A descriptive cross sectional study was carried out at Coronary Care Unit (CCU) of Services Hospital, Lahore. The sample size of 130 patients were enrolled by non-probability consecutive sampling. In this study all male and female patients from 25 to 100 years of age with STEMI who were given SK were included from CCU of Services Hospital, Lahore using non probability consecutive sampling. NLR was calculated. Success of thrombolytic therapy was determined by relief of chest pain & resolution of ≥ 50% ST-elevations (STE) in ECG taken 90 minutes after completion of SK. Results: In this study, there were total 130 cases and out of these 72 (55.38%) were males and 58 (44.62%) were females. High NLR was seen in 43 (33.08%) of the cases. Successful thrombolysis was observed in 99 (76.15%) of the cases. Successful thrombolysis was observed in 29 (67.44%) cases with high NLR and 70 (80.46%) cases with low. There was no significant association of NLR, BMI, smoking, DM and HTN with successful thrombolysis. Practical Implication of this Study: is that in our resource limited country NLR is one of cheapest test to access severity and prognosis so patients with high NLR can be reffered early for intervention even if responded successfully to thrombolysis as complications of STEMI are frequent in high NLR patients as compared to lower NLR. Conclusion: Successful thrombolysis was seen in almost 3/4 cases in acute STEMI. Although a cheaper and readily available prognostic tool, no statistically significant association was found in terms of the admission NLR and the success of thrombolysis. Moreover, there was no significant association in terms of any of the confounders of the study. Keywords: Thrombolysis, Streptokinase (SK), Neutrophil to Lymphocytis Ratio (NLR), ST Segment Elevation MI (STEMI)